Multiple patterns of EEG parameters and their role in the prediction of patients with prolonged disorders of consciousness - Li, Hui; Dong, Linghui; Su, Wenlong; Liu, Ying; Tang, Zhiqing; Liao, Xingxing; Long, Junzi; Zhang, Xiaonian; Sun, Xinting; Zhang, Hao (Frontiers in Neuroscience, 2025)
IntroductionPrognostication in patients with prolonged disorders of consciousness (pDoC) remains a challenging task. Electroencephalography (EEG) is a neurophysiological method that provides objective information for evaluating overall brain function. In this study, we aim to investigate the multiple features of pDoC using EEG and evaluate the prognostic values of these indicators.MethodsWe analyzed the EEG features: (i) spectral power; (ii) microstates; and (iii) mismatch negativity (MMN) and P3a of healthy controls, patients in minimally conscious state (MCS), and unresponsive wakefulness syndrome (UWS). Patients were followed up for 6 months. A combination of machine learning and SHapley Additive exPlanations (SHAP) were used to develop predictive model and interpret the results.ResultsThe results indicated significant abnormalities in low-frequency spectral power, microstate parameters, and amplitudes of MMN and P3a in MCS and UWS. A predictive model constructed using support vector machine achieved an area under the curve (AUC) of 0.95, with the top 10 SHAP values being associated with transition probability (TP) from state C to F, time coverage of state E, TP from state D to F and D to F, mean duration of state A, TP from state F to C, amplitude of MMN, time coverage of state F, TP from state C to D, and mean duration of state E. Predictive models constructed for each component using support vector machine revealed that microstates had the highest AUC (0.95), followed by MMN and P3a (0.65), and finally spectral power (0.05).DiscussionThis study provides preliminary evidence for the application of microstate-based multiple EEG features for prognosis prediction in pDoC.Clinical trial registrationchictr.org.cn, identifier ChiCTR2200064099.